Sistem Konversi Business Process Model Notation ke Unified Modelling Language - Wijaya, Anak Agung Angga; Sukmaaji, Anjik; Sutanto, Teguh (Jurnal Sistem Informasi Universitas Dinamika, 2020)
In the concept of Model Driven Architecture (MDA), There is an Computation Independent Model or known as BPMN and Platform Independent Model or known as UML. In the process of conversion from BPMN to UML is still done manually and it is feared that the quality is not maintained. Because the quality of the results of the conversion depends on who is doing it. This research aims to build a website that can convert it automatically.The process of conversion from BPMN to UML using Business Process Modelling (BPM) data with the Bizagi Modeler format as input.Befor becoming UML, the data is converted to DrawIO with XML type. From DrawIO, UML can be visualized. The process of visualization refers to rules made by Rhazali.The system created can visualize UML from BPM data with BPM input must comply with rules of Thazali, the output will also follow from the above rules and DrawIO is actually a standalone platform but still be displayed in PNG format.